The impact of a referral card-based intervention on intimate partner violence, psychosocial health, help-seeking and safety behaviour during pregnancy and postpartum: a randomized controlled trial - An-Sofie Van Parys; Ellen Deschepper; Kristien Roelens; Marleen Temmerman; Hans Verstraelen (BMC, 2017)
Abstract Background We aimed to investigate the impact of a referral-based intervention in a prospective cohort of women disclosing intimate partner violence (IPV) on the prevalence of violence, and associated outcomes psychosocial health, help-seeking and safety behaviour during and after pregnancy. Methods Women seeking antenatal care in eleven Belgian hospitals were consecutively invited from June 2010 to October 2012, to participate in a single-blind randomized controlled trial (RCT) and handed a questionnaire. Participants willing to be interviewed and reporting IPV victimisation were randomised. In the Intervention Group (IG) participants received a referral card with contact details of services providing assistance and tips to increase safety behaviour. Participants in the Control Group (CG) received a "thank you" card. Follow-up data were obtained through telephone interview at an average of 10 months after receipt of the card. Results At follow-up (n = 189), 66.7% (n = 126) of the participants reported IPV victimisation. Over the study-period, the prevalence of IPV victimisation decreased by 31.4% (P < 0.001), psychosocial health increased significantly (5.4/140, P < 0.001), 23.8% (n = 46/193) of the women sought formal help, 70.5% (n = 136/193) sought informal help, and 31.3% (n = 60/192) took at least one safety measure. We observed no statistically significant differences between the IG and CG, however. Adjusted for psychosocial health at baseline, the perceived helpfulness of the referral card seemed to be larger in the IG. Both the questionnaire and the interview were perceived to be significantly more helpful than the referral card itself (P < 0.001). Conclusions Asking questions can be helpful even for types of IPV of low severity, although simply distributing a referral card may not qualify as the ideal intervention. Future interventions should be multifaceted, delineate different types of violence, controlling for measurement reactivity and designing a tailored intervention programme adjusted to the specific needs of couples experiencing IPV. Trial registration The trial was registered with the U.S. National Institutes of Health ClinicalTrials.gov registry on July 6, 2010 under identifier NCT01158690 ).